THU0531 "BOTHERING TO LISTEN": ENABLING PATIENT AND FAMILY INVOLVEMENT IN CHILDHOOD UVEITIS HEALTHCARE. (June 2019) - Compeyrot-Lacassagne, Sandrine; Twoney, Christine; Petrushkin, Harry; Thomas, Dhanes; Robinson, Emily; Kossarova, Lucia; Solebo, Ameenat Lola
Abstract : Background: Childhood uveitis is a group of heterogenous, potentially blinding inflammatory disorders. Management is complex. There is growing recognition of the importance of actively involving affected children and their families in their own care. Co-designed interventions, developed through active involvement of staff and patients, can provide effective solutions to problems identified by those affected. Objectives: To use findings from a patient and family discussion group to inform the co-designed development of health care processes and interventions. Methods: Five children/young people with uveitis (age ranges 8 to 17), seven parent/carers of children with uveitis and four health care professionals attended a 90 minute discussion group. Main discussion topic was the identification of areas in need of interventions or support structures. Sub-topics were determined a priori using previous PPI and existent research (REFS). They comprised: Direct health care; Impact on families; School, education and peers. Responses were collated. Consent was taken for use of direct quotes from participants. Results: We outline the areas identified by children and families: Direct health care: Four interconnected areas were identified: (1) Transitioning to adult services, (2) peer support (health care services being a valuable site for identifying peers), (3) communication between care structures, and (4) education for families. With regards to family education, there was identification of the need for specific services or interventions around the communication of (4a) diagnosis, (4b) treatment, (4c) likely long term outcomes/prognosis, (4d) and the child's progress. There was also discussion on (4e) the formats used to communicate with families. Impact on families: Participants discussed support around (1) family relationships, (2) the impact of systemic medication. They also discussed (3) a need for recognition of the changing nature of their lived experience as affected families over the disease course and the need for on-going psychologic support especially at presentation to help with acceptance. School, education and peers Participants discussed the need for support around: (1) the impact of treatment on school life, (2) communication with school professionals and peers, (3) impact of visual impairments, (4) managing the visibility/invisibility paradox (ie being made to feel different but also having a disorder which was not externally apparent), and (5) managing adolescence. Conclusion: Through the above approach, we have identified a range of issues affecting our patients and their families. Our findings are similar to those of other groups (1, 2) These lived experiences will be used to inform the co-design of supportive services (patient leaflets, videos, website, psychology intervention) and research on the effectiveness of these interventions in improving the management of affected children and their families. References: [1] Parker DM, Angeles-Han ST, Stanton AL, Holland GN. Chronic Anterior Uveitis in Children: Psychosocial Challenges for Patients and Their Families. Am J Ophthalmol. 2018 Jul; 191:xvi-xxiv [2] Silva LMP, Arantes TE, Casaroli-Marano R, Vaz T, Belfort R Jr, Muccioli C. Quality of Life and Psychological Aspects in Patients with Visual Impairment Secondary to Uveitis: A Clinical Study in a Tertiary Care Hospital in Brazil. Ocul Immunol Inflamm. 2017 Oct 11:1-9. Disclosure of Interests: Sandrine Compeyrot-Lacassagne Grant/research support from: Abbvie, Christine Twoney: None declared, Harry Petrushkin: None declared, Dhanes Thomas: None declared, Emily Robinson: None declared, Lucia Kossarova: None declared, Ameenat Lola Solebo: None declared